1998
DOI: 10.1023/a:1008842613331
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Relative weight may be an important modifiable risk factor for both breast cancer incidence and prognosis. The association between height and breast cancer incidence is more difficult to interpret, but may underscore the importance of early life exposures in the development of breast cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(13 citation statements)
references
References 44 publications
1
12
0
Order By: Relevance
“…Because accurate, early screening and diagnosis are central to survival from breast cancer, insights gleaned from a greater understanding of APO E could aid researchers in identifying those individuals who may be at increased risk of developing breast cancer and ultimately other cancers [44, 45, 51, 53, 129, 130, 131, 132]. Breast cancer survival is improved by targeting factors, particularly certain biological and lifestyle factors, underlying these differences [71, 72, 97, 100, 104, 118, 127, 130, 131].…”
Section: Discussion: Implications For Cancer Preventionmentioning
confidence: 99%
See 3 more Smart Citations
“…Because accurate, early screening and diagnosis are central to survival from breast cancer, insights gleaned from a greater understanding of APO E could aid researchers in identifying those individuals who may be at increased risk of developing breast cancer and ultimately other cancers [44, 45, 51, 53, 129, 130, 131, 132]. Breast cancer survival is improved by targeting factors, particularly certain biological and lifestyle factors, underlying these differences [71, 72, 97, 100, 104, 118, 127, 130, 131].…”
Section: Discussion: Implications For Cancer Preventionmentioning
confidence: 99%
“…Breast cancer survival is improved by targeting factors, particularly certain biological and lifestyle factors, underlying these differences [71, 72, 97, 100, 104, 118, 127, 130, 131]. This is due to the fact that the incidence of breast cancer in the Western world runs parallel to that of the major components of the insulin resistance syndrome, specifically hyperinsulinaemia, dyslipidaemia, hypertension and atherosclerosis [73, 123].…”
Section: Discussion: Implications For Cancer Preventionmentioning
confidence: 99%
See 2 more Smart Citations
“…Obesity has been shown consistently to increase rates of breast cancer in postmenopausal women by 30-50% (Hunter and Willett, 1993;Ballard-Barbash and Swanson, 1996;Trentham-Dietz et al, 1997;Galanis et al, 1998). Some studies have found central adiposity to be an independent predictor of postmenopausal breast cancer risk beyond the risk attributed to overweight alone (Folsom et al, 1993;Kaaks et al, 1998).…”
Section: Breast Cancermentioning
confidence: 99%